Redesign Of BUMDes And MSMEs Marketplace Platform Using User Centered Design Method - Tirta Cahyatama, Muhammad Widya; Wardhana, Ariq Cahya (Universitas Budi Darma, 2025)
This research centers on the redesign of Waroeng Kita, a digital marketplace platform developed to facilitate transactions for Village-Owned Enterprises (BUMDes) and Micro, Small, and Medium Enterprises (MSMEs) in rural Indonesia. An initial usability assessment conducted for this study revealed a low System Usability Scale (SUS) score of 49.16, classifying the platform as